The Effectiveness of the Singing Method in Enhancing Arabic Vocabulary among Students of Rumah Qur’an GIAT - Nashihatud Diniyah Jahro; Hunainah (Al-Mudarris, 2025)
In Islamic educational contexts such as Rumah Qur’an, Arabic vocabulary learning is not merely a linguistic objective but an educational means for fostering meaningful engagement with the Qur’an and Islamic knowledge. As the language of revelation, Arabic is expected to support learners’ comprehension, affective readiness, and disciplined participation in Qur’anic learning. However, in Indonesia, Arabic is not learners’ mother tongue, and instruction in non-formal Qur’anic institutions often relies on memorisation-oriented practices, resulting in limited understanding and low learner engagement. This study investigates the effectiveness of a singing-based instructional method in supporting Qur’anic-oriented Arabic vocabulary learning among primary school students at Rumah Qur’an GIAT. Employing a quantitative pre-experimental one-group pre-test–post-test design, six learners participated in a twelve-session intervention in which selected Arabic vocabulary was taught through structured songs integrated with guided repetition and collective participation. Data were collected through tests and observations and analysed using normalised gain (N-gain).The results indicate a substantial improvement in learners’ vocabulary mastery, with the mean score increasing from 0 in the pre-test to 86.04 in the post-test (N-gain = 0.86, high category). Observational findings further reveal increased enthusiasm, active participation, reduced learning anxiety, and sustained attendance. From an Islamic educational perspective, these findings suggest that singing functions as a pedagogical wasilah that supports cognitive achievement alongside affective readiness and meaningful engagement with Arabic as the language of the Qur’an. The study concludes that effectiveness in Rumah Qur’an instruction should be understood in relation to holistic Islamic educational goals rather than linguistic outcomes alone.